Testing Technical Feasibility in CPS Development Projects - von Hoffen, Moritz; Chasin, Friedrich; Matzner, Martin; Plenter, Florian; Betzing, Jan H (13. Internationale Tagung Wirtschaftsinformatik (WI2017), 2017)
Cyber-physical systems (CPSs) are service systems that connect a product’s physical and computational elements through telecommunication networks. Typically, the processes in CPSs are executed on this physical and computational infrastructure. As the developing of new CPS is costly, testing and validating a CPS’s design at an early stage of development is desirable in order to avoid potential bad investments. The high development and potentially high hardware costs, however, make it difficult to create a full CPS prototype only for testing. This work uses Trkman’s critical success factors of business process management (BPM) as a theoretical lens and identifies “technical-feasibility fit” as an additional complementary success factor. Based on these factors, we develop a method for creating CPS testbeds that allow testing of CPSs at lower costs at an early stage of the development. We demonstrate the method’s application by a case in which we develop a testbed for an electric vehicle charging servic
Keywords: Cyber-physical Systems; Critical Success Factors; Prototyping